The statistical models of machinery milking duration by group milking machines - Кучерук, Володимир Юрійович; Паламарчук, Євген Анатолійович; Кулаков, Павло Ігорович (Eastern-European Journal of Enterprise Technologies, 2014)
Based on the conducted theoretical and experimental studies, the statistical models that establish a functional relationship between statistical characteristics of the milking duration by the group milking machines “Yalinka” and “Parallel” for animal untied housing, and the parameters of milking machines, type of milking machine, statistical characteristics of the animal preparation time and the animal milking time. The proposed models are based on the new approach to estimating the statistical characteristics of the animal preparation time and the animal milking time. This will increase the accuracy of determining the productivity of milking machines in their designing or upgrading, develop a methodology for designing data-measuring systems of the parameters of technological processes of milk production and automatic control of a farm, ensure further development of the theory of such systems. The adequacy of the developed models is higher compared with the existing ones, as confirmed by determining the relative estimation of differences between the results of the theoretical calculations and the experimental data.